PEDAGOGICAL COMPETENCE OF ISLAMIC RELIGIOUS EDUCATION TEACHERS IN ADDRESSING QUR’AN READING PROBLEMS AMONG INDONESIAN JUNIOR HIGH SCHOOL STUDENTS: A PRISMA-BASED SYSTEMATIC LITERATURE REVIEW - I'zatil faqiha; Ali Musa Lubis (Academic Bright Collaboration, 2026)
This study systematically reviews empirical evidence on the pedagogical competence of Islamic Religious Education teachers in addressing Qur’an reading problems among students in Indonesian junior high schools. It responds to fragmented findings on teacher competence, instructional strategies, and student difficulties in Qur’an literacy. The study used a systematic literature review guided by PRISMA 2020. Literature was searched through Google Scholar, Garuda, DOAJ, Crossref, SINTA-indexed journals, and relevant Islamic education journal portals. Studies published between 2019 and 2026 were screened using predetermined inclusion and exclusion criteria. Fourteen articles met the eligibility criteria and were analyzed through descriptive analysis and thematic synthesis. The review found that students’ Qur’an reading problems are multidimensional, including tajwid errors, makhārij al-ḥurūf difficulties, weak hijā’iyyah recognition, low fluency, limited motivation, and unequal family support. PAI teachers’ pedagogical competence was reflected in diagnostic assessment, lesson planning, classroom management, differentiated instruction, formative feedback, and evaluation. The dominant strategies included Iqra’, tahsin, talaqqi, drill, reading deposit, peer tutoring, habituation, audio-visual media, and BTQ/BTA extracurricular programs. The review is limited to 14 Indonesian and English articles published from 2019 to 2026; therefore, the findings cannot be generalized beyond the reviewed corpus. This study proposes an integrated diagnostic-differentiated Qur’an reading pedagogy model linking teacher competence, remedial support, and school–family collaboration.